ANALISIS EKLESIOLOGI TERHADAP EFEKTIVITAS KUNJUNGAN PASTORAL BAGI PERTUMBUHAN KUALITATIF JEMAAT - Manna Y. Sanderan (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2025)
Church growth is often viewed only from a quantitative aspect; however, the true success of ministry lies in the spiritual quality of the congregation, which is influenced by the active role of the pastor. This study aims to analyze the effectiveness of pastoral visitation as a supporting factor for church growth amid changing times that demand an increase in the quality of shepherding ministry. Using a qualitative approach with the library research method, grounded in Rawambaku’s theoretical framework and supported by phenomenological observation, this research explores literature related to the interaction between pastor and congregation. The findings show that the effectiveness of visitation is determined by the pastor’s integrity and attitude of service, which include a servant’s heart, love, and exemplary character in embracing the spiritual needs of the congregation. Through regular visitation, pastors can understand the real condition of the congregation, provide relevant motivation, and restore relationships that directly impact the improvement of both the quality of faith and the quantity of church members. It is concluded that pastoral visitation is an effective strategy to stimulate church growth because it fosters personal spiritual maturity and ensures that every soul is nurtured according to the truth of God’s Word.